Leopardi's hedge and the English garden. Issue 3 (3rd July 2022) - Edo, Miquel
Abstract: Treatises on landscape gardening written toward the end of the eighteenth century and the beginning of the nineteenth, offer clues in deciphering the sense in which Giacomo Leopardi used the term 'romantic situations' in his Zibaldone . In particular, landscape gardeners are revealed to be pioneers in the use of foliage for concealment purposes aimed at stimulating the imagination, but they also help us to understand the role of verticality and quick transitions in a range of 'situations' which, according to the Italian poet, evoke a sense of the infinite. However, while Leopardi carried out a significant agglutination of inherited knowledge, he also implemented his own elements, essential to his poetic concept, that were basically derived from the principle of familiarity and which represented an important source of friction between him and the romantics. Thus, the hedge in his L'infinito can be interpreted as a safety measure, a return to the traditional garden when faced with the dizzying abyss of Romanticism.